2013
DOI: 10.1111/clr.12155
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐infective therapy of peri‐implantitis with adjunctive local drug delivery or photodynamic therapy: 12‐month outcomes of a randomized controlled clinical trial

Abstract: Non-surgical mechanical debridement with adjunctive PDT was equally effective in the reduction of mucosal inflammation as with adjunctive delivery of minocycline microspheres up to 12 months. Adjunctive PDT may represent an alternative approach to LDD in the non-surgical treatment of initial peri-implantitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
248
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(274 citation statements)
references
References 58 publications
8
248
0
11
Order By: Relevance
“…The results of the present study in relation to a decrease in mucosal inflammation, a decrease in BOP and PPD and a decrease in bacterial colony counts are consistent with those of studies by Schar et al 2 and Bassetti et al 40 Therefore, it can be concluded that treatment with laser, drug therapy and treatment with laser in association with photosensitizing dyes yield similar results in the treatment of peri-implantitis. On the other hand, based on the results of the present study only P. gingivalis counts in the control group and A. actinomycetemcomitans, P. gingivalis and T. forsythia counts in the test group decreased significantly; in this context, the bacterial species were similar to those in the study carried out by Bassetti et al 40 In a study, the effect of PDT with toluidine blue on periodontopathogens and biofilm on tooth surfaces was evaluated and it was reported that the use of diode laser beams at a wavelength of 830 nm in association with the use of toluidine blue within periodontal pockets was effective in destroying bacteria and it might be a reliable alternative for antimicrobial treatment in periodontitis. 41 Therefore, the results of the present study are consistent with studies carried on by Shibli et al, 38 Kocher and Mecisel 20 and the study mentioned above.…”
Section: Effectiveness Of Photodynamic Therapy In Treatment Of Peri-isupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study in relation to a decrease in mucosal inflammation, a decrease in BOP and PPD and a decrease in bacterial colony counts are consistent with those of studies by Schar et al 2 and Bassetti et al 40 Therefore, it can be concluded that treatment with laser, drug therapy and treatment with laser in association with photosensitizing dyes yield similar results in the treatment of peri-implantitis. On the other hand, based on the results of the present study only P. gingivalis counts in the control group and A. actinomycetemcomitans, P. gingivalis and T. forsythia counts in the test group decreased significantly; in this context, the bacterial species were similar to those in the study carried out by Bassetti et al 40 In a study, the effect of PDT with toluidine blue on periodontopathogens and biofilm on tooth surfaces was evaluated and it was reported that the use of diode laser beams at a wavelength of 830 nm in association with the use of toluidine blue within periodontal pockets was effective in destroying bacteria and it might be a reliable alternative for antimicrobial treatment in periodontitis. 41 Therefore, the results of the present study are consistent with studies carried on by Shibli et al, 38 Kocher and Mecisel 20 and the study mentioned above.…”
Section: Effectiveness Of Photodynamic Therapy In Treatment Of Peri-isupporting
confidence: 92%
“…The results showed that both treatment modalities were similarly effective in decreasing inflammation of the peri-implant mucosa. Bassetti et al 40 compared drug therapy with minocycline and PDT for the treatment of peri-implantitis. A followup of 12 months showed a significant decrease in the number of sites with BOP, a decrease in probing depth and a decrease in P. gingivalis and T. forsythia counts, with no significant difference between the 2 groups.…”
Section: Effectiveness Of Photodynamic Therapy In Treatment Of Peri-imentioning
confidence: 99%
“…In line with previous findings, there were no differences with regards to IL-6, IL-8, IL-10 (Severino et al 2011), whereas the levels of IL-1β were significantly higher at peri-implantitis, compared to mucositis sites. Further studies also showed that peri-implantitis treatment reduced the PICF levels of IL-1β (Bassetti et al 2013) and TNF-α (de Mendonca et al 2009;Duarte et al 2009a). Studies have also demonstrated that single nucleotide polymorphisms (SNP) in the IL-1 gene may hold an increased risk for the development of peri-implantitis, particularly when combined with smoking (Andreiotelli et al 2008;Bormann et al 2010).…”
mentioning
confidence: 94%
“…Bacteria were cultured anaerobically (85% N 2, 10% H2 and 5% CO2) and grown aerobically at 37°C until logphase growth. Subsequently, bacterial concentrations were adjusted to 0.5 McFarland turbidity standards (equivalent to 1.5×10 8 colony forming units/mL) to perform the experiments described below. The cultivation of Porphyromonas gingival has been described in detail elsewhere 35,36) .…”
Section: Cell and Bacteriamentioning
confidence: 99%
“…Although surgical treatment can restore the bone defect caused by inflammation and various kinds of tissue damage, it is likely to cause major trauma and can easily cause postoperative infections. Moreover, systemic drug therapy for the treatment of peri-implantitis will inevitably produce toxic side effects and adverse reactions in the body 7,8) . Currently, the ability of lasers to kill bacteria makes them highly useful for various dental procedures, such as killing pathogenic bacteria and stimulating bone formation.…”
Section: Introductionmentioning
confidence: 99%